'A Comparison Similar to this': Ossian and the Forms of Antiquity. (June 2016) - Moore, Dafydd
Abstract: This article discusses the ways in which James Macpherson's Poems of Ossian engage with other literary texts within their footnotes, adopting David Hopkins's notion of 'conversing with antiquity' to articulate how Macpherson conveys meaning and seeks to establish poetic characteristics through this interaction with other forms of expression. Attention to this process leads to a discussion of the dramatic qualities of Ossian as discussed by Macpherson and Hugh Blair, concluding with a discussion of Ossian's contribution to an emerging understanding of primitive dramatic forms, comparing the ways in which criticism understands Ossian and Aeschylus during the 1760s and 1770s.